Potencial biotecnológico de microrganismos halotolerantes - Batista, Pedro Victor Morais (Universidade Federal Rural do Semi-Árido, 2019)
Surfactants are substances capable of reducing the superficial tension between imiscible liquids and forming stable emulsions. Most of these is petrochemical in origin and has relativily low cost. However, these synthetic surfactants can lead to different environmental issues related to their use, much as the non-renewable source as their toxicity. Such, in the last decades, there has been a growing interest in the research and commercial use of natural products, specially the ones with microbial origin. These, in turn, have made a stand in the industries to replace the synthetic chemical compunds. Antibiotics, on the other hand, are synthetic or natural molecules capable of killing or disrupting the growth of microrganisms. Their indiscriminated use and the growing consumption of pesticides have been increasing the alarming levels of the microbial resistance, bacterial and fungal, to the antibiotics and pesticides commercially available. Thus, it has become necessary to approach new methods to fight this resistant microbes, pathogenic and phytopathogenic, as well as other plagues. Therefore, it’s important to study the halotolerant microrganisms, the mechanisms that allow this adaptation and the metabolites that can be envolved in this process and their biological activities. These can be interesting commercially because, being from microrganisms that can tolerate normally stressful conditions they can too mantain their biological activities in adverse conditions of pH and temperature. Thereby, the present paper aimed to isolate halotolerant fungi and verify their potential to the production of metabolites with antimicrobial or emulsifying activity. Two strains were chosen for the assays. The methods chosen were the Disk Diffusion and the Emulsification Index, respectively. The production of antimicrobial and bioemulsifying compounds. Hence, two conclusions can be made. It’s necessary to test other strains isolated on this paper, as well as adjusting the culture medium to assess its negative influence and the Carbon and Nitrogen sources.
Monografia
Keywords: Fungos; Antimicrobiano; Emulsificante; Biossurfactante; Halotolerante; Fungi; Halotolerant; Biosurfactant; Emulsifier; Antimicrobial; CIENCIAS BIOLOGICAS::BIOTECNOLOGIA